KARAKTERISTIK BRIKET ARANG SERPIHAN KAYU DENGAN PENAMBAHAN ARANG TEMPURUNG BIJI KARET - Jaisman Putra; Raswen Efendi; Faizah Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study was to determine the characteristics of charcoal briqutte charcoal mixture of wood chips with charcoal rubber seed No- quality according to SNI 01-6235-2000. Research using completely randomized design (CRD) with charcoal treatment comparison wood chips and coconut shell charcoal rubber seed (K0 = 100%: 0%); (K1 = 90%: 10%); (K2 = 80%: 20%); (K3 = 70%: 30%); (K4 = 60%: 40%); (K5 = 50%: 50%). The results showed that variations in mix charcoal wood chips and coconut shell charcoal rubber seeds significantly affect the density,press charcoal briquettes, moisture content, levels of substance evaporates, ash content, bound carbon content and calorific value briquettes. The result showed that the best treatment in treatment K5 namely charcoal briquettes are made with 50% charcoal wood chips and 50% charcoal rubber seed with higher levels of density 0,901 g/cm3, firmness press of 0,466 kg/cm2, the water content of 2,86%, levels of substance evaporates 36,04%, ash content 5,11%, bound carbon content 58,84%, calorific value of 5492,438 cal/g. Keywords: charcoal briquettes, wood chips, rubber seed shell